STUDY ON THE CONFORMATIONS OF p-(NITRO)METHOXYCALIX[4]ARENE AND p-(tert-BUTYL)METHOXYCALIX[4]ARENE USING HIGH LEVEL AB INITIO METHOD - Hanggara Sudrajat; Danis Sriwijaya; Herman Siagian; Ria Armunanto (Indonesian Journal of Chemistry, 2009)
Ab initio calculations have been performed in order to investigate the conformational characteristics of p-(nitro)methoxycalix[4]arene and p-(tert-butyl)methoxycalix[4]arene. The structures of four types (cone, partial cone, 1,2-alternate and 1,3-alternate) of conformers for each compound have been optimized by ab initio method at the restricted Møller-Plesset fourth-order perturbation (RMP4) level of theory using 6-311G and 6-311G++(d,p) basis sets. General trends in relative stabilities of p-(nitro)methoxycalix[4]arene and p-(tert-butyl)methoxycalix[4]arene are similar and decrease in following order: partial cone > cone > 1,3-alternate > 1,2-alternate. The calculated results of the most stable conformation of partial cone structure agree with the reported NMR experimental observations.